Educational Messages on the Teng-tengan Tradition of Kaliwungu People in the Context of Coastal Cultural Communication (Catharsis, 2022)
Teng-tengan is a tradition from the Kaliwungu community in Kendal Regency. Teng-tengan tradition takes the form of a lantern and appears to celebrate birthday of Prophet Muhammad every year. (1) How is the form of the teng-tengan tradition of Kaliwungu community, Kendal Regency? (2) How are the messages integrated in the teng-tengan tradition of Kaliwungu community, Kendal Regency? (3) How educational messages are communicated through teng-tengan tradition for the people of Kaliwungu, Kendal Regency. With interdisciplinary studies, the research method and approach were qualitative. According to the findings of the first study, the teng-tengan tradition form was a lantern made up of a pentagonal star, a ship, a moon, a crescent star, and, more recently, the shape of the cartoon character of Spongebob. Second, the educational messages embedded in teng-tengan tradition include spiritual, moral, social, and unity messages. Third, educational messages were communicated through teng-tengan tradition through presentation activities, festivals, and teng-tengan parades.